3D automatic target recognition for future LIDAR missiles - Kechagias-Stamatis, Odysseas; Aouf, Nabil; Richardson, Mark A. (IEEE, 2017)
We present a real-time three-dimensional automatic target recognition approach appropriate for future light detection and ranging-based missiles. Our technique extends the speeded-up robust features method into the third dimension by solving multiple two-dimensional problems and performs template matching based on the extreme case of a single pose per target. Evaluation on military targets shows higher recognition rates under various transformations and perturbations at lower processing time compared to state-of-the-art approaches.